APLIKASI GAME CAK INGKLING BERBASIS ANDROID - Terttiaavini Terttiaavini; Ari Kaspriyanto; Hartini Hartini (UNIVERSITAS INDO GLOBAL MANDIRI)
Game has been the one thing that is in our daily lives. Formerly only used as a means of entertainment games alone, but now the game has become wide functions, such as games can be used as a learning tool, a business area, and competed as one of the sport by professionals. Game development platform can also be viewed directly by the public, at first only games played on computer and console but has now entered the era of mobile game android and Windows Phone. A distinct advantage is the portability of mobile game play, that player can play games anywhere they want as long as they have mobile devices capable of running mobile games.Game developed a modification of the traditional game smack ingkling aimed at children aged 6-13 years , This game has 3 levels where each level the player will be given about the question. The design of this game uses the android operating system. In addition, this game was built using a programming language actionscrpit contained in Adobe Flash CS6. In the development of this game using MDLC (Multimedia Development Life Cycle) with five stages that have been made that concept, design, material colecting, assembly, and testing. Design and manufacture of this game is aimed at preserving the traditional game smack ingkling to be a trend back in the era of smartphones today.Keywords: Traditional games, hopscotch, MDLC, Android.